2019
DOI: 10.3390/rs11192328
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ZiYuan-3 Multispectral and Stereo Data for Modeling Aboveground Biomass of Larch Plantations in North China

Abstract: Data saturation in optical sensor data has long been recognized as a major factor that causes underestimation of aboveground biomass (AGB) for forest sites having high AGB, but there is a lack of suitable approaches to solve this problem. The objective of this research was to understand how incorporation of forest canopy features into high spatial resolution optical sensor data improves forest AGB estimation. Therefore, we explored the use of ZiYuan-3 (ZY-3) satellite imagery, including multispectral and stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…This research showed that the fusing data of high-resolution multispectral bands with medium-resolution multispectral images can improve the accuracy of GSV estimation for Chinese pine and larch plantations in northern China. Some studies have proved that the red band performs much better than other bands when using optical images for AGB or GSV estimation [28,31], which is consistent with the finding of this study that the Red_Landsat image fused by the GF-2 red band with the Landsat 8 multispectral data leads to larger R 2 and smaller RMSEr values than other fused images, including the fusion image Pan-Landsat.…”
Section: The Role Of Data Fusion In Gsv Estimationsupporting
confidence: 91%
See 3 more Smart Citations
“…This research showed that the fusing data of high-resolution multispectral bands with medium-resolution multispectral images can improve the accuracy of GSV estimation for Chinese pine and larch plantations in northern China. Some studies have proved that the red band performs much better than other bands when using optical images for AGB or GSV estimation [28,31], which is consistent with the finding of this study that the Red_Landsat image fused by the GF-2 red band with the Landsat 8 multispectral data leads to larger R 2 and smaller RMSEr values than other fused images, including the fusion image Pan-Landsat.…”
Section: The Role Of Data Fusion In Gsv Estimationsupporting
confidence: 91%
“…The k-fold cross validation method is useful for both classifications and estimation without extra data required (where, k is the number of sample plots). Therefore, we used the leave-one-out cross-validation for calculating determination coefficient (R 2 ), adjusted R 2 , RMSE and relative RMSE (RMSEr) between the estimated and observed values to assess the models' prediction performance [28,31]. They were calculated by:…”
Section: Evaluation Of Modeling Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, we also explored texture measures using the gray level co-occurrence matrix (GLCM) within the size of the sample plot (20 × 20 m) to extract textural images from the CHM data. The texture measures included correlation, contrast, dissimilarity, entropy, homogeneity, second-order moment, and variance [53,54]. These metrics and the corresponding forest AGB of sample plots were exported to SPSS for further analysis.…”
Section: Collection and Processing Of Airborne Lidar Datamentioning
confidence: 99%